Zionism and Socialism in the Centennial of Peruvian Independence - Cadenas Erazo, Patricia (2020)
In this work, it is revealed the mutual influence and reciprocal contribution between socialist Zionism and socialism through an explicative outline of the nationalism-internationalism interaction. It implies a historical reference from social reality by means of a description of the cultural, intellectual and political activities that, jointly, the socialist Jews carried out with Jose Carlos Mariategui, the leader and founder of socialism in Peru. They were twinned by their common ideal of social emancipation and struggle against any oppression kind during the second half of the 1920 decade, around the celebrations for the Centennial of Independence. For that reason, it is also examined the similarities or shared elements in the ideology and political thought of the concerned parties, to establishing finally the specific link between socialist Zionists and Mariategui.